Dopamine beta hydroxylase (DBH) plasma activity in childhood mental disorders - Paclt, Ivo; Koudelová, Jitka; Pacltova, Dagmar; Kopeckova, Marta (Neuro endocrinology letters, 2009)
BACKGROUND: Developmental study of dopaminergic and noradrenergic systems in child psychiatric disorders are rare. DBH activity is one of noradrenergic biochemical marker that is correlate in psychiatry to clinical and genetic data. OBJECTIVES: The main aim of the present study was to measure DBH activity at the onset of acute schizophrenia and depressive disorder in children and adolescents without pharmacological treatment and to compare these values with DBH activity in healthy controls. The authors also investigated untreated ADHD children. METHODS: We examined 42 control healthy children, 15 children non-treated with acute schizophrenia, 15 non-treated children with acute depressive disorders and 30 non-treated ADHD children, all in age 7-14. Plasma DBH level was provided by Nagatsu (1972; 1974). Depressed children were reexamined after clinical remission. RESULTS: DBH activity is statistically significantly decreased in non-treated depressive disorder and ADHD in children and adolescents. DBH activity is normalised during antidepressant therapy in child depression. Child schizophrenia patients present with normal DBH activity. CONCLUSION: These results are similar to the results that have been observed in adult patients with schizophrenia and depression and in previous studies of DBH activity in children with ADHD. These results also indicate hypoactivity of the noradrenergic system in children with ADHD and depression.
Keywords: Attention Deficit Disorder with Hyperactivity; Humans; dítě; Dopamine beta-Hydroxylase; Child; hyperkinetická porucha; Female; lidé; Biomarkers; zvířata; duševní poruchy; biologické markery; ženské pohlaví; Male; Adolescent; Mental Disorders; Animals; dopamin-beta-hydroxylasa; mužské pohlaví; mladiství